O PIBID na formação de professores: trajetórias e vivências de estudantes cotistas do Curso de Pedagogia - SOUSA, Scarlet Cristina Silva (2021)
This dissertation addresses the importance of the Institutional Program of Teaching Initiation Scholarships (PIBID) in the process of initial training and teacher reflexivity of teachers from the trajectories and experiences of students who have entered the Pedagogy course of the Federal University of Maranhão (UFMA) through the quota system. We adopted theoretical bases on teacher education in the research, in addition to considering the educational policies elaborated by the federal government until 2020 and that based the conceptions presented in the dissertation. The results were obtained through the application of the bibliographic approach associated with research instruments such as semi-structured interviews and questionnaires with the six research subjects who were selected based on the identification of those who entered the pedagogy course through the quota system and who were active in the PIBID Pedagogy Subproject of UFMA. The conceptual categories and theoretical contribution are concentrated in authors such as Tardif (2013, 2014), Bourdieu (2014, 2007), Schön (2000, 1995, 1992), Ghedin (2012), Tanuri (2000), Saviani (2009, 2008), Gatti (et. al. 2011), Perrenoud (2006) among other authors who deal with the same perspective of discussion, in addition to the normative bases that govern the formative processes of education professionals. The results of the research reveal that the development of policies focused on the formative processes of teachers has undergone several changes over the years, with stagnation and cuts of funds that would be directed to train teachers in undergraduate or continuing education courses. The results reveal that the PIBID was inserted in society as a policy of teacher training with the objective of training qualified professionals to work in basic education and improving the quality of teaching in public schools. The collected data indicate that, considering the PIBID as an educational policy, there was a change in the ways that students see the initial training of teachers in UFMA from the moment they are inserted in the school as an integral part of the program. We verified that the Pedagogy Subproject of UFMA provided the development of criticality, teaching feeling and reflexivity of students from the pedagogical mediation between school and University through pibid.